Intramodal perceptual grouping modulates multisensory integration: Evidence from the crossmodal dynamic capture task - CHAN, JASON (Elsevier, 2005)
We investigated the extent to which intramodal visual perceptual grouping influences the multisensory integration (or grouping) of auditory and visual motion information. Participants discriminated the direction of motion of two sequentially presented sounds (moving leftward or rightward), while simultaneously trying to ignore a task-irrelevant visual apparent motion stream. The principles of perceptual grouping were used to vary the direction and extent of apparent motion within the irrelevant modality (vision). The results demonstrate that the multisensory integration of motion information can be modulated by the perceptual grouping taking place unimodally within vision, suggesting that unimodal perceptual grouping processes precede multisensory integration. The present study therefore illustrates how intramodal and crossmodal perceptual grouping processes interact to determine how the information in complex multisensory environments is parsed.
PUBLISHED
Keywords: Psychology